Effect Of Peak Current And Pulse On Time On The Coating Layer Thickness Using Electrical Discharge Coating - Liew, Pay Jun; Mohammad Zainudin, Norhazeratul; Yap, Ching Yee; Mohamad, Noraiham; Jingsi Wang (Penerbit Akademia Baru, 2021)
The present study focused on the surface modification of aluminum 6061 by using electrical discharge coating (EDC) with powder suspension. The effects of peak current (Ip) and pulse on time (Ton) on the coating layer thickness were investigated. This study used Tungsten powder as an additive and mixed it with the kerosene oil and surfactant Span 83. The results indicated that peak current and pulse on-time significantly affected the coating layer thickness. The thinnest coating layer was observed at 3A, 150 μs, while the thickest coating layer with an average value of 17.239 μm was obtained at parameter 4A and 250 μs. In conclusion, the high value of peak current and longer pulse duration on time increased the thickness of the coating layer.